(3cJGH GdfLQe TGgi aj GdYHGOGJs - (3GdfLQe TGgjs
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje EYde Cf GdhGLH Ydi Gdecda eYQaI Gddg JYGdi dbhdg JYGdi (B( (3heG NdbJ GdLf hGdEfS EdG djYHOhf (B) (3Ci jYQahf s
(3BNQgG (B:s
(3aUd ai CdaGX GdcaQ hdG jLhR GdYOhd Yf XhGgQ GdbQBf hGdMOjK hGdbhd HCf XhGgQ GdfUhU eJQhcI Hd dgG eYGf dGjYdegG EdG Gddg JYGdi hGdQShd caQ dCfg fai GdTQjYI HGdcdjI Je GdcJGH s
(3HgG fXGe GdJYbjHIs
(3HChdgG agQS ddcJGHs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdESdGejs